Promoting Continuous Professional Development Among Academics from A Vocational College by Using A Practical Workshop Based on Arduino Technology - Swart, Arthur, James; Hertzog, Pierre, Eduard (Advances in Science, Technology and Engineering Systems Journal Vol. 5, No. 2, 452-459 (2020), 2020)
The internet of things has resulted in the design and development of many electronic sensors that need to be integrated with various technologies. Engineering academics need ongoing training relating to this integration as they need to subsequently teach their students. This relates to continuous professional development. The purpose of this article is to illustrate how engineering academics from a vocational college have been able to engage with the theory and practice of sensor integration with Arduino technology, thereby strengthening or reconstructing their conceptual knowledge of these electronic components. A case study is used where experts in electrical engineering designed and facilitated an academic development workshop (2 days in duration) to address a need for continuous professional development. Eighteen academics from a local vocational college attended this workshop where the first goal was to determine their conceptual knowledge of 10 electronic components using an electronic responsive system (pre-test). The second goal was to facilitate a “hands-on” laboratory session where academics had to physically integrate various sensors with an Arduino microcontroller. A post-test online questionnaire was then used to determine their conceptual knowledge again, in order to ascertain the impact of the workshop. Results indicate that their conceptual knowledge was reconstructed with regard to the purpose and use of capacitors, Zener diodes, transformers, ultrasonic sensors, reed switches and passive infrared receivers. A problematic question arose relating to photocells in the first workshop that was held in 2017, which was resolved by the facilitators prior to offering a second workshop in 2018. Positive feedback was received from the participants regarding the relevance and presentation of the workshops. The novelty of this work relates to the design of a practical workshop where all participants are engaged to either strengthen, or reconstruct, their conceptual knowledge regarding electronic components that may be integrated with Arduino technology.
Article
Keywords: Practice; e-learning; Pre-post test